Escape from the strength-to-toughness paradox: Bulk ceramics through dual composite architectures. Issue 8 (July 2018) - Monteverde, Frédéric; Melandri, Cesare; Failla, Simone; Grohsmeyer, Ryan J.; Hilmas, Gregory E.; Fahrenholtz, William G.
Highlights: For the first time, DC composites in the ZrB2 -MoSi2 system were synthesized and densified. DC composites exhibited properties that were not possible using conventional approaches. DC architectures made of strong and stiff granules into a ductile matrix reached strength and toughness of up to 440 MPa and 11.5 MPa √m. Abstract: This paper describes an approach to escape from the classic strength-toughness trade-off in bulk ceramics using the dual composite architectural concept. The key questions addressed by the research were: can dual composite architectures be fabricated? -how do dual composite architectures affect the physical properties of ceramics? -do dual composite architectures affect the mechanical behavior of composites? -do dual composite architectures have increased damage tolerance at elevated temperatures? These questions were answered positively. Reinforcing granules dispersed in loose powder mixtures were hot-pressed to obtain fully dense dual composite architectures with target overall composition. Defined sub-composites (labeled granule and matrix) of similar compositions, but differing engineered microstructures, were successfully retained. The brittle-to-ductile transition of MoSi2 above 1400 K enabled the simultaneous increase in both strength and toughness, and values of up to 440 MPa and 11.5 MPa√m, respectively, were experimentally determined at 1773 K.